2008
DOI: 10.1210/me.2008-0102
|View full text |Cite
|
Sign up to set email alerts
|

Interplay and Effects of Temporal Changes in the Phosphorylation State of Serine-302, -307, and -318 of Insulin Receptor Substrate-1 on Insulin Action in Skeletal Muscle Cells

Abstract: Transduction of the insulin signal is mediated by multisite Tyr and Ser/Thr phosphorylation of the insulin receptor substrates (IRSs). Previous studies on the function of single-site phosphorylation, particularly phosphorylation of Ser-302, -307, and -318 of IRS-1, showed attenuating as well as enhancing effects on insulin action. In this study we investigated a possible cross talk of these opposedly acting serine residues in insulin-stimulated skeletal muscle cells by monitoring phosphorylation kinetics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 69 publications
3
49
1
Order By: Relevance
“…Increased IRS-1 serine phosphorylation has been shown to interfere with both tyrosine phosphorylation of IRS-1 (50) and the association between IRS-1 and p85␣ subunit of PI3K necessary for full Akt activation (51). Whether this is due to the increase in phosphorylation of IRS-1 (Ser-312) or a combination of serine sites in IRS-1 is not proven here.…”
Section: Discussionmentioning
confidence: 84%
“…Increased IRS-1 serine phosphorylation has been shown to interfere with both tyrosine phosphorylation of IRS-1 (50) and the association between IRS-1 and p85␣ subunit of PI3K necessary for full Akt activation (51). Whether this is due to the increase in phosphorylation of IRS-1 (Ser-312) or a combination of serine sites in IRS-1 is not proven here.…”
Section: Discussionmentioning
confidence: 84%
“…There is, however, no a priori reason to expect that the same mechanism of insulin resistance that we have identified in adipocytes from human beings is operational in other tissues or even in adipocytes from other species. We (3, 56, 58 -60) and others (61,62) have previously found that phosphorylation of IRS1 at serine 307 in response to insulin is coupled to a positive feedback. In particular, our earlier mathematical model analysis showed that a positive feedback best explained data for the whole system (3).…”
Section: Discussionmentioning
confidence: 91%
“…The importance of cell type and experimental conditions implicating negative or positive effects is illustrated by the phosphorylation of IRS1 at serine 312 (human sequence, corresponding to serine 307 in murine sequence), an established negative effect in different experimental setups (34 -36) that in a knock-in experiment eventually was found to have a positive effect on insulin signaling in mice in vivo (37). Examining different aspects of insulin signaling we (10 -13) and others (14,15) have previously found that phosphorylation of IRS1 at serine 307 in response to insulin is associated with a positive feedback. The systems approach we used herein demonstrates that a positive feedback to IRS1 can best explain the experimental data for the whole system.…”
Section: Measured Variablementioning
confidence: 99%